CITRA FISIOLOGIS DAN PSIKOLOGIS TERUNA-TERUNI BALI DALAM NOVEL SUKRENI GADIS BALI KARYA PANDJI TISNA - I Wayan Nitayadnya (Balai Bahasa Sulawesi Tengah, 2015)
The result of this research are expected to be useful in founding and developingattitude and mindset of teruna teruni Bali in particularly, and to young generationof Indonesia in generally for the future challenges. The method used in collectingdata is library research. The results of the analysis showed that (1) the physiological aspect of image of teruna teruni Bali from are beautiful and handsome, and (2) the psychological aspect of image of teruna teruni Bali related with Godness relationship is the piousness teruna teruni and concerning the nature is protecting nature; relationship with them self is the image of teruna teruni who are apathetic, hopeful, and strong convictions.